Pengaruh Profitabilitas, Ukuran Perusahaan, Leverage, dan Pengungkapan CSR terhadap Nilai Perusahaan - Elyana Putri Nur Fitri; Tantina Haryati (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to examine and analyze the effect of profitability, firm size, leverage and CSR disclosure on firm value. The population used in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. This research is an explanatory research with a quantitative approach. This study uses secondary data in the form of an annual report. The sampling technique used purposive sampling method. Based on the criteria or considerations that have been determined, 32 companies were obtained as research samples. The analysis technique in this study uses partial least squares with the help of the SmartPLS program. The results of this study indicate that profitability has a positive and significant effect on firm value, firm size has a positive and significant effect on firm value, leverage has a positive and insignificant effect on firm value, and corporate social responsibility (CSR) has a positive and insignificant effect on firm value. Keywords: profitability, firm size, leverage, csr disclosure, firm value